Optimization of Electroporation-Enhanced Intradermal Delivery of DNA Vaccine Using a Minimally Invasive Surface Device - Lin, Feng (Mary Ann Liebert, Inc., 2012)
In vivo electroporation (EP) is an efficient nonviral method for enhancing DNA vaccine delivery and immunogenicity in animals and humans. Intradermal delivery of DNA vaccines is an attractive strategy because of the immunocompetence of skin tissue. We have previously reported a minimally invasive surface intradermal EP (SEP) device for delivery of prophylactic DNA vaccines. Robust antibody responses were induced after vaccine delivery via surface EP in several tested animal models. Here we further investigated the optimal EP parameters for efficient delivery of DNA vaccines, with a specific emphasis on eliciting cellular immunity in addition to robust humoral responses. In a mouse model, using applied voltages of 10–100 V, transgene expression of green fluorescent protein and luciferase reporter genes increased significantly when voltages as low as 10 V were used as compared with DNA injection only. Tissue damage to skin was undetectable when voltages of 20 V and less were applied. However, inflammation and bruising became apparent at voltages above 40 V. Delivery of DNA vaccines encoding influenza virus H5 hemagglutinin (H5HA) and nucleoprotein (NP) of influenza H1N1 at applied voltages of 10–100 V elicited robust and sustained antibody responses. In addition, low-voltage (less than 20 V) EP elicited higher and more sustained cellular immune responses when compared with the higher voltage (above 20 V) EP groups after two immunizations. The data confirm that low-voltage EP, using the SEP device, is capable of efficient delivery of DNA vaccines into the skin, and establishes that these parameters are sufficient to elicit both robust and sustainable humoral as well as cellular immune responses without tissue damage. The SEP device, functioning within these parameters, may have important clinical applications for delivery of prophylactic DNA vaccines against diseases such as HIV infection, malaria, and tuberculosis that require both cellular and humoral immune responses for protection.